KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENCIPTAKAN PEMBELAJARAN DARING YANG EFEKTIF DI SMK NEGERI 4 MALANG - Ari Setiawan; Dwi Fitri Wiyono; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The Coronavirus pandemic has raised a ruckus around town, including Indonesia, throughout the previous 2 years or something like that. Coronavirus has had many effects, particularly on instructive foundations. During this Coronavirus period, PAI educators at SMK Negeri 4 Malang made new developments and imagination in web based advancing by using learning media (innovation). The technique utilized in this study is a subjective spellbinding strategy. Information assortment procedures as meetings, perceptions, and documentation. With respect to information examination strategy in this study utilizing Miles Huberman. That's what the outcomes showed: (1) The imagination of educators in involving web based learning media during the Coronavirus pandemic in PAI subjects at SMKN 4 Malang was by using innovation. For example, utilizing WhatsApp media, Google Homeroom media, Youtube media, Google web media, Google meet media, making your own media, to be specific Power point. (2) The imagination of educators in involving web based learning strategies during the Coronavirus pandemic in PAI subjects at SMKN 4 Malang, specifically the educator utilizes the Q & A technique so web based learning is fascinating and not exhausting, so understudies assume a functioning part in web based learning, (3) Snags that looked by instructors in completing web based getting the hang of during the Coronavirus pandemic in PAI subjects at SMKN 4 Malang were challenges in passing material on to understudies, utilization of web organizations, absence of comprehension of instructors on web gadgets, restricted time in instructing, educator showing experience, not yet prepared. managing changing circumstances that are generally done up close and personal now on the web or distance learning.